2007
DOI: 10.1590/s0100-204x2007000200017
|View full text |Cite
|
Sign up to set email alerts
|

Diferimento de pastos de braquiária cultivares Basilisk e Marandu, na região do Cerrado

Abstract: Resumo -O objetivo deste trabalho foi avaliar o acúmulo de forragem e o valor nutritivo de pastos de Brachiaria decumbens e Brachiaria brizantha, diferidos em fevereiro e março e pastejados durante o período seco. O delineamento experimental foi o de blocos ao acaso com parcelas subdivididas. As parcelas principais foram constituídas pelas espécies de Brachiaria e as subparcelas pela época de diferimento. Os pastos diferidos em fevereiro apresentaram maiores massas de matéria seca total (MST) e de matéria seca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
28

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 1 publication
3
22
0
28
Order By: Relevance
“…This result is similar to those obtained by Euclides et al (2007), who observed a forage productivity of 6.5 t ha -1 of total dry mass at the beginning of the dry season from Brachiaria brizantha cultivated on a Dystrophic Red Latosol in an Awi-Cfa transitional climate in Campo Grande, MS, Brazil. However, the total dry-mass production varied among cuttings.…”
Section: Methodssupporting
confidence: 90%
“…This result is similar to those obtained by Euclides et al (2007), who observed a forage productivity of 6.5 t ha -1 of total dry mass at the beginning of the dry season from Brachiaria brizantha cultivated on a Dystrophic Red Latosol in an Awi-Cfa transitional climate in Campo Grande, MS, Brazil. However, the total dry-mass production varied among cuttings.…”
Section: Methodssupporting
confidence: 90%
“…Owing to the negative correlation with the age of the plants, some loss in their nutritional value is inevitable. It is important to choose a species that adapts to the conditions of the dryland region in order to successfully manage the deferred pastures (EUCLIDES et al, 2007). In addition, the species must produce thin, high leaf stalk/stem, and loss of nutritional value over time should be slow (SANTOS et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Assim, em pastagens diferidas, mesmo com elevada massa de forragem acumulada, a estrutura pode interferir no consumo dos animais, a resultar em quedas de desempenho. As plantas mais indicadas para a prática de diferimento são aquelas, cujo VN sofre redução lenta ao longo do tempo, com baixo acúmulo de colmo e boa retenção de folhas verdes (EUCLIDES et al, 2007). Isso inclui espécies do gênero Brachiaria (decumbens, capimmarandu e capim-xaraés), Cynodon (capins estrela, coastcross e tifton) e Digitaria (capim-pangola).…”
Section: Diferimento De Pastagensunclassified